Production of Urban Space in Conflict Areas - Contested Binaries and Spatial Injustice in Palestine - Samman, Maha (MAJ - Malaysia Architectural Journal, 2025)
A continuous debate exists over whether politics shape the direction of urban planning or if urban planning itself influences political dynamics. In conflict areas, however, politics utilizes urban planning as a tool for domination and control. In Palestine, the colonial Israeli political apparatus has used urban planning to create conflicting urban spaces that have impacted the Palestinian social, economic, legal, and temporal aspects of daily lives. The research aims to assess how this conflicting urban space has created multi- and inter-layered contested binaries by answering the research question of how colonial urban planning has been used to produce an urban space characterized as contested binaries in Palestine. This shall be addressed using thematic qualitative and spatial methodologies, and by covering four different spatial perspectives influenced by colonial urban planning which have created countering impacts on peoples. The first is on urban settlements and how conflict hinders the development of one urban area while enhancing imposed new urban settlements creating conflicting urban identities in the same place. The second is on the frames and boundaries of existence and perishing where elements of segregation such as the Segregation Wall and the checkpoints create zones for existence and others for expendable life. The third is on spacio-temporal dynamics of infrastructure and how two levels are produced: one facilitating the lives of one group of people while disrupting the lives of another people and therefore affecting the loss and gain of time in everyday life. The last perspective accentuates at times of friction and confrontation, where the binaries are vertically reflected on urban resilience and urban warfare whether produced underground or aboveground. Analysis of these four perspectives shall provide some insights on how these binaries create a state of spatial injustice and drain available resources with ecological costs on the environment.